THE EFFECTIVENESS OF PLAGIARISM ONLINE EDUCATION AND HOW TO AVOID IT IN IMPROVING STUDENTS' UNDERSTANDING OF PALGIARISM - Agussalim , Amirah Aminanty; Ahmad , Astiti Tenriawaru; Rasyid , Nurfajriyanti; Musawwir, Musawwir (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
Plagiarism is an academic violation that is currently very often encountered in higher education environments, especially among students. This research was conducted with the aim of testing the effectiveness of the educational module on Plagiarism and How to Avoid It. This research uses a quasi-experimental method with a one group pre-test and post-test design. There were 119 participants who were active students at the Faculty of Psychology, Makassar State University. The intervention carried out was psychoeducation using online media. Pre-test and post-test measurements using questions about understanding plagiarism and how to avoid it. The results of statistical analysis using Paired Samples T-Test showed a significance value (2-tailed) p = 0.001 (p < 0.05). The results of this research show that the Plagiarism and How to Avoid It intervention is effective in increasing students' understanding of plagiarism and ways to avoid it